Data for Distribution of Vascular Plants (Tracheophytes) of Urban Forests and Floodplains in Tyumen City (Western Siberia) - Anatoliy A. Khapugin; Igor V. Kuzmin (Data, 2022)
Tyumen City is a large city in Western Siberia. This territory has ecological problems, which are typical to many cities around the world, including the loss of biodiversity and environment, habitat pollution, and others. This data paper presents for the first time the plant species composition of 11 natural forest and floodplain areas in Tyumen City. In a city, forests provide a refuge for both threatened plants and weeds (including alien species). In these ecosystems, unique communities are being formed, where both threatened and alien plants can co-occur. Within the city’s area, forests serve as separate green “islands” among urbanized landscapes. A total of 11 forest and floodplain areas have been studied based on field surveys conducted by the authors of the paper in 2020–2022. The obtained data (8742 observations representing 434 species, accepted subspecies, and hybrids belonging to 270 genera and 74 families) serve as a basis for the modern flora of Tyumen City, its conservation, and counteraction to the introduction of alien plants.